Effect of physical activity on prevention of postpartum depression: A dose-response meta-analysis of 186,412 women - Yuan, Mengqi; Chen, Hongyang; Chen, Dongmei; Wan, Donggui; Luo, Fan; Zhang, Chenyang; Nan, Yunxin; Bi, Xiaoning; Liang, Jing (Frontiers in Psychiatry, 2022)
Background: Physical activity (PA) is considered a favorable prevention factor for postpartum depression (PPD), but evidence defining a corresponding dose-response relationship is lacking. This meta-analysis was performed to assess the protective effects of PA on PPD and define a potential dose-response relationship between them. Methods: PubMed, Medline, Embase and Web of Science were searched from 1968 to May 2022. Only randomized control trials (RCTs) and prospective studies were considered, and the PICOS tool was used to identify eligible articles based on the inclusion and exclusion criteria. Effect-size estimates were unified as odds ratio (OR) and 95% confidence interval (CI). We calculated the ORs and their 95% CI for studies that did not report them using the Practical Meta-Analysis Effect Size Calculator. Results: A total of 23 studies were eligible, including 14 RCTs and 9 prospective cohort studies. The overall analysis showed a positive association between PA and PPD prevention (adjusted OR=0.73; 95% CI: 0.61 to 0.87; P< 0.001), with statistically significant. Subgroup analyses indicated that studies conducted in Europe demonstrated a significant correlation between PA and reduced PPD (adjusted OR=0.85, 95% CI: 0.76 to 0.95, P=0.004). With regard to PA type, sports activity was associated with PPD symptoms relieve (adjusted OR=0.89, 95% CI: 0.78 to 1.00, P<0.001), while work (adjusted OR=1.05, 95% CI: 0.37 to 2.97, P=0.065) and household activities (adjusted OR=1.16, 95% CI: 0.89 to 1.52, P=0.986) contributed to greater risk of PPD. Our dose-response analysis revealed a reverse J-shaped trend between ascending PA duration and PPD incidence. Conclusions: This meta-analysis identified PA as a potential intervention to reduce the risk of PPD. The dose-response analysis revealed that at least 90 minutes of PA per week could efficiently decrease the risk of PPD.